Unusual Vascular Supply to Extensor Digitorum Brevis. Issue 4 (April 2016) - De Silva, Dinuksha; Hsieh, Frank; Gillies, Rowan
Abstract : Summary: Lower limb reconstruction after a traumatic event has always been a challenge for plastic surgeons. The reliability of vessel integrity postinjury often drives us away from a local reconstructive option. With the advancement of computed tomography angiogram, it can not only demonstrate the continuation of major vessels but also helps to map the vascular supply at a perforator level. We hereby report an incidentally identified anatomical variant with dual dominant blood supply to the extensor digitorum brevis muscle from an extra branch of anterior tibial artery originated at midtibial level. This variant was picked up preoperatively by computed tomography angiogram and confirmed intraoperatively to be one of the dominant supply. We took advantage of this unusual anatomy by basing our reconstruction on this branch and hence spared the need to terminalize distal dorsalis pedis artery.